PENGEMBANGAN MEDIA PEMBELAJARAN LAPBOOK BERBASIS KEARIFAN LOKAL PADA MATA PELAJARAN IPAS SISWA KELAS IV SDN 2 SURODADI - Yuli Artika; Hamdan; Yetty Trisnayanti (Linggau Journal Science Education (LJSE), 2026)
This study aims to develop a lapbook media based on local wisdom for the Social Sciences subject in 4th grade at SDN 2 Surodadi, as well as to produce lapbook media that is valid, practical, and effective. This research is of the Research and Development type using the Four-D model. The research subjects were 4th grade students of SDN 2 Surodadi, 4th grade teachers, and expert validators. Data collection techniques included interviews, questionnaires, and tests. Based on the analysis results from three experts, including language, material, and media experts, it was shown that the lapbook media based on local wisdom meets the valid criteria, with an average score of 0.91. Meanwhile, the practicality assessment analysis from students and teachers showed that the lapbook media based on local wisdom meets the practical criteria, with an average score of 91.6%. From the effectiveness test analysis, an N-gain (g) of 0.56 was obtained with a medium classification, which means that the lapbook media based on local wisdom has medium effectiveness. Based on the research results, it was concluded that the lapbook media based on local wisdom has proven to be valid, practical, and effective for learning science and social studies in 4th grade at SD Negeri 2 Surodadi.